2017
DOI: 10.1371/journal.pone.0190064
|View full text |Cite|
|
Sign up to set email alerts
|

Functional implications of hexameric assembly of RraA proteins from Vibrio vulnificus

Abstract: RNase E has a pivotal role in the degradation and processing of RNAs in Escherichia coli, and protein inhibitors RraA and RraB control its enzymatic activity. The halophilic pathogenic bacterium Vibrio vulnificus also expresses orthologs of RNase E and RraA—RNase EV, RraAV1, and RraAV2 (herein renamed as VvRNase E, VvRraA1, and VvRraA2). A previous study showed that VvRraA1 actively inhibits the ribonucleolytic activity of VvRNase E by interacting with the C-terminal region of VvRNase E. However, the molecular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 23 publications
(40 reference statements)
0
3
0
Order By: Relevance
“…The late embryogenesis abundant (LEA) proteins have been shown to be related to desiccation tolerance (Boudet et al, 2006). Stress-related genes have been profiled (Shu et al, 2013; Song et al, 2015, 2017; Albornos et al, 2017), and myo-inositol and proline have been shown to be involved in Medicago drought tolerance (Zhang et al, 2014). The salinity tolerance is related to the induction and expression of highly regulated antioxidant mechanisms (Mhadhbi et al, 2011).…”
Section: Medicago Truncatula As a Model To Study The Molecular Basis mentioning
confidence: 99%
“…The late embryogenesis abundant (LEA) proteins have been shown to be related to desiccation tolerance (Boudet et al, 2006). Stress-related genes have been profiled (Shu et al, 2013; Song et al, 2015, 2017; Albornos et al, 2017), and myo-inositol and proline have been shown to be involved in Medicago drought tolerance (Zhang et al, 2014). The salinity tolerance is related to the induction and expression of highly regulated antioxidant mechanisms (Mhadhbi et al, 2011).…”
Section: Medicago Truncatula As a Model To Study The Molecular Basis mentioning
confidence: 99%
“…Furthermore, no variations were observed in either swimming or swarming motility among the strains ( Fig. 2C ), which contrasts with the decreases in swimming and swarming motility observed in the RraAV1 mutant strain of V. vulnificus ( 12 , 24 ).…”
Section: Resultsmentioning
confidence: 59%
“…It has been reported that the overexpression of RraAV1 results in a moderately slower growth rate than that of the WT in V. vulnificus ( 7 , 24 ). However, in the present study, changes in the rraA transcript abundance did not significantly affect the growth of LBS in rich media ( Fig.…”
Section: Resultsmentioning
confidence: 99%